Interrelationship of the Kinin System, Nitric Oxide and Eicosanoids in the Antigen-Induced Arthritis in Rabbits - Fernando Alfonso Salamea Palácios; Gilberto Santos Novaes; Maria Luiza Guzzo; Ieda Maria Magalhães Laurindo; Suzana Beatriz Verissimo de Mello (Mediators of Inflammation)
The aim of the present study was to investigate the interrelationship of the kinin system, nitric oxide and eicosanoids in the acute phase of antigen-induced arthritis (AIA) in rabbits. The arthritis was induced in immunized rabbits and the following parameters were evaluated 24 hours later: leukocyte influx (total and differential white cell count), vascular permeability (Evans's blue method), and synovial PMN cell infiltrate. PGE2 and LTB4 (radioimmunoassay) levels were quantified in the synovial fluid. The animals were pre-treated with 20 mg/kg/day during 14 days with L-NAME or D-NAME and/or Enalapril (0.12 mg/ kg/day-14 days), and/or the B2 antagonist of Bradykinin HOE 140 (0.9 mg/kg). Our results showed that L-NAME was effective in the prevention of AIA with reduction of all inflammatory parameters analyzed. Enalapril partially reverted the L-NAME anti-inflammatory effects. The simultaneous treatment with HOE 140 abolished this reversion and returned the inflammatory parameters to the levels observed in L-NAME treated animals. Our results suggest that pressoric alterations induced by L-NAME could not account for all its anti-inflammatory action in this model of experimental arthritis. Additionally the contribution of the kinin system in AIA was characterized as well as its interaction with eicosanoids and nitric oxide.